Leading connected classrooms engaging the hearts and souls of learners - Dillon, Robert 1974- (Corwin, 2015)
Help your students find and keep the joy in learning! When creative use of technology meets outstanding teaching, incredible learning happens. This insightful guide is for all educators ready to move into a new commitment to true learning. Principal and respected digital educator Robert Dillon shows readers how to: * Use student engagement to promote authentic, thoughtful learning * Learn how 16 innovative connected educators provided incredible learning opportunities for their students * Implement new technology resources and strategies for all classrooms and grade levels * Help students build critical thinking skills and gain confidence in their unique voices "This book combines the voices of seasoned connected educators with great suggestions for growth for those new to building connected classrooms as well as those educators ..